2018
DOI: 10.18805/ijare.a-320
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of some physiological responces to salinity and normal conditions in Sugar Beet 

Abstract: This study was carried out in the Agricultural Research Center of West Azerbaijan, Iran in 2016. In this research, variations in different physiological and yield traits measurement of total dry weight, shoot fresh weight, shoot dry weight, root fresh weight, root dry weight, relative water content, relative water loss, root length, leaf area, root/shoot ratio, specific leaf weigh, sodium content, potassium content and proline were investigated in normal and saline condition. The results indicated that in sali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
1
1
1
Order By: Relevance
“…To minimize the negative effect of salt stress, the plant developed phenotypic plasticity ( Rewald et al., 2012 ). Contrary to what has been reported in previous studies, that the root/shoot ratio increased in stress conditions ( Khorshid et al., 2018 ; Rahimi et al., 2021 ), in our investigation, this ratio decreased for all P treatments. This reduction was more relevant at 45 ppm of P for Ortho-A followed by Poly-B and Ortho-B which were similar for both doses of P. Thus, biomass was more allocated in shoots than in roots.…”
Section: Discussioncontrasting
confidence: 99%
“…To minimize the negative effect of salt stress, the plant developed phenotypic plasticity ( Rewald et al., 2012 ). Contrary to what has been reported in previous studies, that the root/shoot ratio increased in stress conditions ( Khorshid et al., 2018 ; Rahimi et al., 2021 ), in our investigation, this ratio decreased for all P treatments. This reduction was more relevant at 45 ppm of P for Ortho-A followed by Poly-B and Ortho-B which were similar for both doses of P. Thus, biomass was more allocated in shoots than in roots.…”
Section: Discussioncontrasting
confidence: 99%
“…On the other hand, Mohican and Orthega exhibited better performance as NaCl levels increased. Our results confirmed the findings of Mostafavi (2012), Jamil & Rha (2004) and Khorshid et al (2018). They determined a significant reduction in root, shoot length and seedling fresh weight due to increasing salinity.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, relative water content, electrolyte leakage and chlorophyll content were recently used for indicators of salinity in barley (Ashraf 2004), in wheat (Farooq & Azam 2006, Jamali et al 2015. In sugar beet, decreased relative water content and chlorophyll content in leaves (Khorshid et al 2018) and increased electrolyte leakage under NaCl were reported by Wang et al (2017) but Skorupa et al (2019) determined no changes in chlorophyll content. Due to the controversial reports and lack of sufficient researches, physiological traits needs to be confirmed by comparing salt stress sensitive and tolerant cultivars in sugar beet.…”
Section: Introductionmentioning
confidence: 99%